Analysis the Effect of Economic Growth, Population, Labor Force Participation Rate, and Open Unemployment Rate on Poverty Rate in Malang Regency - Alida Noverina; Drs. Ec. Marseto, M.Si (International Journal of Economics, Business and Innovation Research, 2024)
Poverty is a shared issue that must be addressed seriously, as it describes the condition of an individual unable to live a life considered humane. This study examines the impact of economic growth, population size, labor force participation rate (LFPR), and open unemployment rate (OUR) in Malang Regency. Using secondary time series data from 2004-2023, a quantitative descriptive approach with multiple linear regression analysis was employed, processed using SPSS 25 software. The research findings indicate that simultaneously, the variables of population size and open unemployment rate significantly affect poverty levels. Specifically, economic growth does not affect poverty levels, population size has a significant negative effect on poverty, labor force participation rate has no effect on poverty, and open unemployment rate has a positive effect on poverty. This study provides insights into the dynamics affecting poverty levels in Malang Regency, highlighting the crucial role of population size as an initial factor in creating open unemployment, which reduces an individual's effectiveness in working and increases poverty levels. Understanding these factors can help policymakers develop strategies to reduce poverty and promote economic stability.